1986
DOI: 10.1144/gsl.sp.1986.021.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Mesozoic-Cenozoic clastic depositional environments revealed by DSDP Leg 93 drilling on the continental rise off the eastern United States

Abstract: Summary Prior to Deep Sea Drilling Project (DSDP) Leg 93 (1983), drill data along the continental rise of the Atlantic margin of the United States were quite limited compared to those of the adjacent continental shelf and the deeper, more seaward expanses of the North American Basin. Interpretations of the geologic history and of processes that controlled sedimentation along the rise were strongly dependent on studies of seismic reflection profiles. DSDP Leg 93 drilled deep holes on both the lower an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Summerhayes & Masran (1983, p. 475) also observe that 'sediments first became commonly laminated in the Valanginian... as sea level was rising' (also Lini et al 1992, p. 380). Wise et al (1986) find that the late Valanginian sees the first occurrence of 'black to dark grey carbonaceous claystone' interbeds at DSDP Site 603B in the NW Central Atlantic; these beds form up to 33% by thickness during the Valanginian and Hauterivian, but are interpreted as distal organic-rich turbidites, perhaps redeposited from an up-slope oxygen minimum zone (Wise et al 1986, p. 41). Waples (1983, p. 969) considers that (initially scattered) definitive evidence of true deep-basin anoxia in the North Atlantic does not occur until at least the late Hauterivian; however, Summerhayes & Masran (1983, p. 476) note that on a carbonatefree basis, maximum TOC values actually increase progressively from the Berriasian to the Hanterivian (as sea level rises), reaching values of up to 6-10% (but mostly less than 2%).…”
Section: Central Atlantic and European Tethysmentioning
confidence: 99%
“…Summerhayes & Masran (1983, p. 475) also observe that 'sediments first became commonly laminated in the Valanginian... as sea level was rising' (also Lini et al 1992, p. 380). Wise et al (1986) find that the late Valanginian sees the first occurrence of 'black to dark grey carbonaceous claystone' interbeds at DSDP Site 603B in the NW Central Atlantic; these beds form up to 33% by thickness during the Valanginian and Hauterivian, but are interpreted as distal organic-rich turbidites, perhaps redeposited from an up-slope oxygen minimum zone (Wise et al 1986, p. 41). Waples (1983, p. 969) considers that (initially scattered) definitive evidence of true deep-basin anoxia in the North Atlantic does not occur until at least the late Hauterivian; however, Summerhayes & Masran (1983, p. 476) note that on a carbonatefree basis, maximum TOC values actually increase progressively from the Berriasian to the Hanterivian (as sea level rises), reaching values of up to 6-10% (but mostly less than 2%).…”
Section: Central Atlantic and European Tethysmentioning
confidence: 99%
“…These distorted blocks could denote slumped overbank deposits, which in turn would indicate the presence of well-defined fan channels. As noted by Wise et al (1986), similar features were found to be characteristic of cores taken at overbank Sites 617 and 620 in the middle Mississippi fan, where high sedimentation rates promoted locally unstable slopes (Coleman et al, 1985).…”
Section: Cape Hatteras Deep-sea Fan Complexmentioning
confidence: 54%
“…It was to narrow this data gap that DSDP Leg 93 drilled a series of deep holes on both the lower and upper continental rise, a task which was continued by DSDP Leg 95. Our Leg 93 team results, which have been made available as expeditiously as possible (see Leg 93 Staff, 1983;Leg 93 Scientific Party/Leg 94 Scientific Party, 1984;von Rad et al, 1984;van Hinte et al, 1985a, b;Wise et al, 1986), have expanded our understanding of the geologic history and the processes which have shaped the North Atlantic continental rise. Four holes were attempted, but no penetration was achieved at Hole 603A (see Table 1).…”
Section: Modified Cruise Planmentioning
confidence: 97%
See 2 more Smart Citations